(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
One of the least studied themes about the Mexican Revolution has been the exile. A few people left the country with Porfirio Díaz in 1911, but after Victoriano Hurta’s coup d‘état and the radicalization of the Mexican Revolution, there was a true exodus. The article shows Francisco Bulnes’s ordinay life, a well known “Porfirista”(Porfirio Díaz’s supporter), who lived exiled in Havana, the capital of Cuba, between 1915 and 1920. Not only does it show one aspect of the Revolution, but also the social and political atmosphere in Cuba in the 1910s and 1920s. When Bulnes was 68 years old he moved to New Orleans where he lived for a little more than one year and later, in December 1915, he settled down in Havana where he lived exiled for five years. Bulnes’s situation was not easy due to the political problems in the island which gave place to the imprisoning of several exiled Mexican and because of the impact the First World War made on the region.